Perlindungan Hukum Terhadap Pemegang Polis Asuransi Dalam Menyelesaikan Sengketa Klaim Asuransi Jiwa - Salsabilla; Amelia Putri Permata Sari; Gitra Permata; Safanny Aprilya Putri, Helfira Citra (CV. ITTC INDONESIA, 2024)
Legal protection for life insurance policy holders is very important because the policy holder is the only written evidence as proof that the insurance has occurred. The contents of the life insurance agreement are an indication of what is happening. The life insurance agreement is binding through an insurance agreement which is proven by the life insurance policy that there has been a transfer of risk, for example life insurance or loss insurance to the insurance company. The research used is descriptive analytical, namely describing all conditions and facts and analyzing current implementation. Related to this method is library-based research which uses library materials such as books, applicable laws and regulations, documents and other media that can be used as data material or theoretical basis for problems in research.